Accurate Respiratory Rate Assessment for Women in Labor. Issue 5 (September 2021) - Bernstein, Samantha L.
Abstract : Respiratory rate assessment for women in labor is not always accurate or consistent. Our guest columnist, Samantha Bernstein, a perinatal patient safety expert, presents a summary of the evidence on why respiratory rate data are vital to maternal and fetal wellbeing during labor and offers suggestions for improving practice.